2013
DOI: 10.4317/jced.51178
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic management of open apex using MTA and platelet - rich fibrin membrane barrier: A newer matrix concept

Abstract: Objectives: Endodontic management of open apex using MTA and platelet – rich fibrin membrane as an apical matrix barrier. Study design: An immature tooth with pulpal necrosis and periapical pathology imposes a great difficulty to the endodontist. Endodontic treatment options for such teeth consist of conventional apexification procedure with and without apical barriers. This article demonstrates the use of an apical matrix barrier in form of a platelet rich fibrin membrane for stabilization of MTA in root end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Platelet-rich Fibrin (PRF) is a matrix of platelet and leukocyte cytokines embedded in autologous fibrin and used as an apical membrane [61] (Fig. 1).…”
Section: Mta and Platelet Rich Fibrin (Prf) Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Platelet-rich Fibrin (PRF) is a matrix of platelet and leukocyte cytokines embedded in autologous fibrin and used as an apical membrane [61] (Fig. 1).…”
Section: Mta and Platelet Rich Fibrin (Prf) Membranementioning
confidence: 99%
“…It facilitates neo-angiogenesis, vascularization and graft survival. It also accelerates the healing of wound edges preventing the extrusion of the material into the periodontal tissues, allowing a favourable response by periodontal tissues [61].…”
Section: Causes Crown Discolourationmentioning
confidence: 99%
See 1 more Smart Citation
“…To form the apical matrix barrier, a platelet-rich fibrin (PRF) membrane was prepared as follows: 12 mL of whole blood was intravenously drawn from the patient' s right antecubital vein and centrifuged at 3000 rpm for 10 min. This formed three layers in the tube : a layer of red blood cells at the bottom, an acellular plasma at the top, and a PRF clot in the middle8) . The PRF clot was separated and pressed between two gauzes to create a Preoperative panoramic radiograph of the 13-year-old female patient.…”
mentioning
confidence: 99%
“…Shivashankar et al 24 , Khetarpal et al 25 and Rudagi & Rudagi and apical bone formation. Shivashankar et al 24 concluded that revitalization of necrotic infected immature tooth is possible under conditions of total canal disinfection and PRF is an ideal biomaterial for pulp-dentin complex regeneration. Use of MTA and PRF for the repair of the perforation defect and Grade II furcation has resulted in long term results with regeneration of the lost periodontium in furcation area.…”
mentioning
confidence: 99%